A high-accuracy Stewart–lift platform based on a programmable logic controller – comparative case studies - Pawuś, Dawid; Witek, Michał; Klar, Łukasz; Bochenek, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The study reports the results of a comparative analysis of advanced high-accuracy Stewart-lift platform along with a comparative study of dynamic control. A control system powered by a programmable logic controller (PLC) was used. The properties of the system were described using a dynamic model using the Lagrange method. The real object was verified by performing several tests and comparing them using quality indicators. The results of verification tests conclusively demonstrate the system suitability for applications within industrial automation and robotics systems.